Factors for Resource Conservation in Present-Day Conditions - Aleksandrovna Vershinina, Anna; Aleksandrovna Zhdanova, Olga; Vladimirovna Plyasova, Svetlana; Karapetovna Arabyan, Knarik (International Journal of Engineering and Technology, 2018)
This paper puts forward and confirms the following hypothesis: at any level, resource conservation policy is grounded in a set of factors for resource conservation, which influence the achievement of target indicators. To confirm the hypothesis, the authors explore the concept of resource conservation and investigate the issue of effective and rational use of resources both at the level of production and consumption by particular entities and at the level of the national economy as a whole. The paper examines the role played by Russia in maintaining environmental security globally and explores some of the key challenges and threats to environmental security at the legislative level. The authors propose a classification of factors for resource conservation that could help employ relevant methods for managing resource conservation, reduce resource consumption, and achieve a better environmental situation.Â Â
Keywords: Ecology; Environmental security; factors for resource conservation; Resource conservation policy.